Factors influencing the success of information systems in flood early warning and response systems context - Waleed A. Hammood; Salwana Mohamad @Asmara; Ruzaini A. Arshah; Omar A. Hammood; Hussam Al Halbusi; Mohammed Abdullah Al-Sharafi (Universitas Ahmad Dahlan, 2020)
Flash flood is a natural disaster that often occurs after heavy rain, and it is getting more common nowadays. The flood early warning and response system (FEWRS) can be installed to minimize the level of damage and the number of casualties due to flood by providing accurate and reliable flood data. Unfortunately, the existing number of studies detailing on the factors affecting the efficiency of FEWRS in flood disaster is quite limited. The above issue is addressed in the current work, which involves conducting a comprehensive literature review on the factors that drive the effectiveness of information systems (IS) in FEWRS. The current analysis was based on the Wymer and Regan's standards. From the 66 factors identified from the previous studies on IS adoption, the most significant factors affecting the effectiveness of FEWRS are: system quality, information quality, user satisfaction, service quality, use, perceived usefulness, intention to use,net benefits, perceived ease of use,compatibility, user experience, relative advantage, complexity, perceivedrisks, educational quality, and confirmation, these factors can be constructed to the success model to address the effectiveness of FEWRS in disaster management.